On the map of the Turkish world in Turkish textbooks - Coban, Ismail; Polatcan, Faruk (Geomatik Journal, 2025)
The place of mother tongue teaching in transferring culture to new generations is very important. The transfer of written and oral culture, prominent in mother tongue teaching, is also supported by the transfer of visual culture. With the amendment added to the Ministry of National Education Textbooks and Educational Tools Regulation in 2024, it is stated that the Turkish world map should also be included in the textbooks. Again, in the Secondary School Turkish Course Curriculum, which was changed in 2024, it is stated that elements related to the Turkish world should be included in the text preferences and textbook content. In this study, which was carried out in line with the renewed Regulation and Program, to determine the content of the map added to the middle school 5th-grade Turkish textbooks, the scanning method, one of the qualitative research methods, was used. The Turkish world map on the last pages of the 5th grade Turkish textbooks was evaluated using the document review method. In the examination, it was determined that the Turkish world map included state names, autonomous state and region names, geographies where Turkish communities live, city names, sea names, strait names, lake names, and river names. It was determined that the map did not include the names of some states that are important neighbors of Turkey and the Turkish world; the names of cities, rivers, and straits that are important for the Turkish world; and the names of regions that contain cultural and civilizational works of the Turkish world. It was concluded that the map should be re-prepared by competent cartographers and Turkologists in the field and that both cartography and Turkology were needed.
Keywords: Turkish world; Map; Textbook; Curriculum